The Impact of Using Cooperative Language Learning Technique in Enhancing Students' Writing Skill in EFL Classes Case of Second Year Bachelor Students of English at the University of Souk-Ahras - REMADNIA Soulef. (My University, 2022)
Abstract The present study aims at investigating the impact of using cooperative language learning in enhancing the writing skill of second-year Bachelor students of English Language at Mohamed Cherif Messaadia University, in Souk-Ahras. This integrated technique to learning is meant to engage learners in the different classroom activities to develop their writing proficiency. In this regard, a questionnaire was distributed to second-year bachelor students of the English language in order to test the main hypothesis that suggests the possibility of improving writing skill through the use of cooperative language learning. The significance of this study is to clearly illustrate how cooperative learning may upgrade the teaching-learning experience by facilitating teachers' everyday work in classrooms and making learners more aware and conscious of their learning. The data gathered proves that cooperative learning is truly effective in enhancing the writing skill. Thus, the research's main hypothesis is confirmed. Therefore, cooperative language learning should be considered as a teaching technique in the writing classes, and both teachers and students should be trained to work with its different methods and techniques to effectively overcome writing difficulties that students face and then develop their writing abilities.